2022
DOI: 10.1186/s12886-022-02340-y
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface squamous neoplasia in Northern Thailand: a 16-year review

Abstract: Purpose To evaluate clinical characteristics, treatments, and outcomes in patients with ocular surface squamous neoplasia (OSSN) at a tertiary center in Northern Thailand. Methods Patients diagnosed with either corneal-conjunctival intraepithelial neoplasia (CIN) or squamous cell carcinoma (SCC) from May 2000 to December 2015, were recruited. The patients’ demographics, symptoms, clinical characteristics, cytopathology, treatments, and outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Higher levels of UV-B exposure in Malawi, Thailand, and India (with population-weighted average daily ambient UV radiation levels of 5,019 J/m 2 , 4,862 J/m 2 , and 4,514 J/m 2 , respectively) seem to correlate with the higher proportions of invasive disease in these regions, while Taiwan (2,908 J/m 2 ), which has similar levels of UV-B radiation to our population (3,206 J/m 2 ) had a comparable low rate of invasive disease to that of our study [12, 22, 26‒28]. However, this trend did not hold across all countries, as the recent New Zealand-based study by Hossain et al (2022) had higher rates of invasive disease despite substantially lower UV-B radiation (2,487 J/m 2 ), while Shields et al (2017) found significantly higher rates of invasive disease despite similar levels of radiation exposure (2,736 J/m 2 ) [11, 18].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Higher levels of UV-B exposure in Malawi, Thailand, and India (with population-weighted average daily ambient UV radiation levels of 5,019 J/m 2 , 4,862 J/m 2 , and 4,514 J/m 2 , respectively) seem to correlate with the higher proportions of invasive disease in these regions, while Taiwan (2,908 J/m 2 ), which has similar levels of UV-B radiation to our population (3,206 J/m 2 ) had a comparable low rate of invasive disease to that of our study [12, 22, 26‒28]. However, this trend did not hold across all countries, as the recent New Zealand-based study by Hossain et al (2022) had higher rates of invasive disease despite substantially lower UV-B radiation (2,487 J/m 2 ), while Shields et al (2017) found significantly higher rates of invasive disease despite similar levels of radiation exposure (2,736 J/m 2 ) [11, 18].…”
Section: Discussionsupporting
confidence: 56%
“…UV-B radiation exposure also potentially plays a role in this trend [20]. The younger mean age of diagnosis in Malawi, Thailand, and India could potentially be explained by the higher rates of UV radiation exposure in these regions, a known pathogenic risk factor for OSSN development [22, 26‒28]. Conversely, Taiwan had a comparable higher mean age of diagnosis to our study, reflecting the similar levels of UV-B radiation in that region [12].…”
Section: Discussionsupporting
confidence: 47%
“…This is in keeping with large studies and follows the pathophysiology of OSSN, which is thought to originate from the limbal stem cells [ 7 , 13 16 ]. OSSN is also most commonly reported in the interpalpebral space, with the nasal quadrant mostly affected [ 14 , 15 ]. This is hypothesised to be due to the amplification of UVB radiation on the nasal limbus [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The large number of pigmented lesions in our study is likely due to our predominantly black African cohort where more pigmentation has been reported than in white patients [ 17 ]. Pigmentation in OSSN lesions has a significant regional variation and has been reported at 1% in a white cohort, 9% in a Thai cohort, 78% in an Indian cohort, and 55% in our mostly black African cohort [ 14 , 15 , 18 ]. Mild and moderate pigmentation likely represents complexion associated melanosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation